Phased Impacts of China’s Dual-Credit Policy on R&D - Li, Xu; Xiong, Qing Y. (Frontiers in Energy Research, 2021)
As a sustainability policy in emerging markets, the dual-credit policy was implemented in China to promote automakers expanding investment in research and to development, and ultimately achieve the energy-saving and emission-reduction goals of the auto industry. We regard dual-credit policy as a quasi-natural experiment, use the difference-in-difference model to divide Chinese automakers into an experimental group (passenger vehicle group) and a control group (commercial vehicle group), and analyze the impacts of dual-credit policy in brewing period (2014-2016) and implementation period on the scale, intensity and structure of research and development investment. We found that the dual-credit policy has significantly promoted the research and development investment of automakers, and the heterogeneity of automakers have a moderating effect on the policy effects. In addition, we also found that there are certain differences in the significance and stability of the effects of dual-credit policy during brewing period and implementation period. Finally, we presented some management insights into the response to the dual-credit policy.